Party volatility in Peru: Rethinking democratic institutionality - Seifert Bonifaz, Manuel (2016)
This article presents a contribution to the approach when with political parties at the sub-national level. After the political parties crisis of 1989-1993 the Peruvian political system was reconfigured. Within this framework, regional and municipal elections were held (2002-2014) and showed how regional movements became hegemonic electoral actors at the subnational level. However, these elections also exhibited a high party volatility, both for regional and national parties. Thus, the present work seeks to rethink our approach to the Peruvian party system and democratic institutionality, assuming that instability is its essential characteristic and, from this, to understand democratic consolidation under this scenario.